Engineering enhanced cellobiohydrolase activity - Larry E. Taylor (Nature Portfolio, 2018)
Cellobiohydrolases (CBHs) are critical for natural and industrial biomass degradation but their structure–activity relationships are not fully understood. Here, the authors present the biochemical and structural characterization of two CBHs, identifying protein regions that confer enhanced CBH activity.